No Social Distancing: Challenges and Collaboration in the Use of Computer-Mediated Learning (CML) Experienced by Selected Students in the Master of Education in English as Second Language Course during the Time of the Coronavirus - Amy Luz U. Catalan (Pusat Studi Bahasa dan Publikasi Ilmiah, 2021)
The COVID-19 pandemic forced higher learning institutions to shift to the remote mode paving the way for computer-mediated learning (CML), a new yet familiar method of engagement between the teacher and the students. The main purpose of this study is to discuss the challenges experienced and the manner of peer collaboration as students maximized the teaching and learning process in such a setup. The study is descriptive-qualitative by design. It involves a thematic analysis of the corpus collected from selected participants who shared their experiences on CML. The respondents of this study were enrolled in the Master of Education in English as a Second Language (M.Ed.-ESL) course. Before distributing the questions, the researcher explained the features of CML. She, then, proceeded to secure their consent. After which, she coded and extracted the sub-themes and themes. These were collated, categorized in a matrix, and validated. Verbatim statements to support the results were provided. Results showed the themes on challenges are internet connectivity, online tools and gadgets, motivation, emotional and mental health, limited interaction, environmental distractions, physical wellness, time management, and access to learning resources. Themes on collaboration showed that the participants work and interact through online applications and tools, adjust to peers’ schedules, and provide mutual peer support. The results also showed challenges even while they were collaborating such as internet connectivity, unfamiliar forms of class participation, untimely feedback, among others. This study furnished valuable insights in overcoming the difficulties that students encounter in CML especially on the affective aspect of the CML. This should improve collaboration between the mentors and the students, and among the students themselves, which could be beneficial in adapting to this new setup. An audit of CML tools describing how to navigate CML could assist the teachers and students to overcome the challenges, especially on collaboration, and banish a sense of isolation that is posed by this mode of learning.